2011
DOI: 10.2478/v10038-011-0043-5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the "Red Win" Effect in Sports: A Hypothesis of Erroneous Perception of Opponents Dressed in Red - Preliminary Test

Abstract: Purpose. Psychological research indicates that, in contact sports, the results of sports competitions might be influenced by the color of an athlete's uniform (especially the color red). However, previous research has not yet experimentally verified whether this hypothesis might be a consequence of perceptual distortion caused by moving objects of a certain color, such as red. Therefore, the aim of this study was to determine the effect of an object's color on the efficiency of performing simple tasks in a bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
1
14
1
Order By: Relevance
“…One of the general research trends in modern color psychology is sport psychology (see Sorokowski & Szmajke, 2011). Many teams create their image with a reference to color.…”
Section: Introductionmentioning
confidence: 99%
“…One of the general research trends in modern color psychology is sport psychology (see Sorokowski & Szmajke, 2011). Many teams create their image with a reference to color.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the color red is frequently associated with fire and blood which can lead to excitement and fear (Kaiser, 1984;Camgöz et al, 2004). Sorokowski and Szmajke (2011) found that red could improve performance in a target-hitting task. This result indicated that participants attempting to hit a red moving objects can achieve better performance than participants attempting to hit blue or black targets.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42] Thus, the players might be more difficult to detect on a similar-colored background, as already suggested by Rowe et al 36 However, experimental research has already emphasized the significance of color brightness for color detection and appearance on chromatic backgrounds. [39][40][41][42][43] Considering a lower detection rate and speed for darker colors (minor values of lightness), black kits were also expected to carry an advantage for attacking and defending teams on offside judgments because of the increased complexity of their perceptual detectability. The results of the current study supported this hypothesis and tied in with the finding of Sorokowski and Szmajke, 43 who reported a significantly lower detection rate for moving black balls versus red balls in an "arcade" game (hitting moving objects presented on a computer screen).…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43] Considering a lower detection rate and speed for darker colors (minor values of lightness), black kits were also expected to carry an advantage for attacking and defending teams on offside judgments because of the increased complexity of their perceptual detectability. The results of the current study supported this hypothesis and tied in with the finding of Sorokowski and Szmajke, 43 who reported a significantly lower detection rate for moving black balls versus red balls in an "arcade" game (hitting moving objects presented on a computer screen). They proposed the possibility of an association between a moving object's color and perceptual errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation